STABLE DENTAL MIRROR - INVENTION - Bahammam, Laila A. (Pakistan Oral & Dental Journal, 2021)
The present invention is about a stable dental mirror that is placed on the rubber dam frame (RDF) used during dental treatment. The mirror is able to be moved and rotated through 360 degrees and does not need to be held, thus freeing the dentist’s hands which will cause less muscle stress and fatigue. Also, it does not have closely spaced joints, which yields good mirror stability with minimum vibration. Furthermore, it is easy to use and clean because it includes one fixed piece without any sharp projections.